(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Heat transmission in the fabric is strongly related to the thermal comfort, which plays an important role when designing fabrics. In this work, a heterogeneous model constructed according to the internal structure of five woven fabrics was developed to study the heat transmission through fabrics. In this model, heat can transfer along the longitudinal and transverse direction of warp and weft yarn at different rate base on the inputted boundary conditions and constants, such as mass density, specific heat and thermal conductivity. In addition, heat transmission occurring in the contacting interface between the warp and weft yarn was also considered. The validity of this model was then confirmed by the high consistency between the thermal resistance obtained from experiment and simulation. The simulation results suggested that heat mainly transfers inside the same yarn, with only a very small portion of heat exchange between the warp and weft yarn via their contacting region. Besides, the calculated fabric thermal resistance is obviously affected by the size of contacting area between fabric and heat source.